Online digital games for Arabic language learners - Sahrir, Muhammad Sabri (2016)

(untitled)
Digital Game-based Learning (DGBL) has been among teaching and learning aids in many disciplines of knowledge. This project presents an educational product of online digital educational games for Arabic language learners. This product was specifically designed based on the language syllabus used by the pre-university students of non-Arabic native speakers at International Islamic University Malaysia (IIUM). This educational digital games in learning Arabic are being used by the learners since 2011 until now. This digital games prototype is using web-based platform with Raptivity e-authoring tool in the prototype development process with a conpendium of 34 various language games for Arabic language learners.